Prevalence and Association of Physical Activity with Obesity: An Urban, Community-Based, Cross-Sectional Study - Shavinder Singh; Rajesh Issac; Anoop Ivan Benjamin; Seema Kaushal (Wolters Kluwer Medknow Publications, 2015)
Aim: To study levels of physical activity and various measures of obesity and their association in an urban population. Study Design: Cross sectional. Materials and Methods: One thousand and forty-seven individuals between the ages 25-64 years systematically sampled from a community-based population database were contacted through a house-to-house survey. We adopted the WHO STEPS guidelines for conducting this study. Anthropological measures collected were height, weight, and waist and hip circumference. Results: Physical Activity (PA) levels declined with age and the decline was greater among females. The Pearson's correlation coefficient for age against PA among males was found to be negative and weak (r = -0.104) and that among females was found to be similar (r = -0.206). The prevalence of obesity was higher among females (28.8 %) than among males (13.3 %) and the difference was statistically significant. There was a progressive increase in abdominal obesity with age in both genders. The prevalence of overweight and obesity was higher among individuals with low levels of PA as compared to those with high levels of PA. Conclusion: Sedentary behavior is prevalent in more than half of the current study sample. This was more so with increasing age, female gender and increasing obesity. PA is an important component on long-term weight control, and therefore adequate levels of activity should be prescribed to combat the obesity epidemic. Habitual moderate physical activity may be beneficial in preventing excess accumulation of fat.